Case Series: Acute Hemorrhagic Encephalomyelitis After SARS-CoV-2 Vaccination - Ancau, Mihai; Liesche-Starnecker, Friederike; Niederschweiberer, Johanna; Krieg, Sandro M.; Zimmer, Claus; Lingg, Charlotte; Kumpfmüller, Daniela; Ikenberg, Benno; Ploner, Markus; Hemmer, Bernhard; Wunderlich, Silke; Mühlau, Mark; et al. (Frontiers in Neurology, 2022)
We present three cases fulfilling diagnostic criteria of hemorrhagic variants of acute disseminated encephalomyelitis (acute hemorrhagic encephalomyelitis, AHEM) occurring within nine days after the first shot of ChAdOx1 nCoV-19. AHEM was diagnosed using magnetic resonance imaging, cerebrospinal fluid analysis and brain biopsy in one case. The close temporal association with the vaccination, the immune-related nature of the disease as well as the lack of other canonical precipitating factors suggested that AHEM was a vaccine-related adverse effect. We believe that AHEM might reflect a novel COVID-19 vaccine-related adverse event for which physicians should be vigilant and sensitized.